Adsorbent from waste and natural deposits for paraquat removal in water - Zakaria, N. F. (2016)
Studies on the removal of frequently used herbicide for controlling broad-leafed weeds, Paraquat Dichloride (PQ) has been carried out intensively. Waste from steelmaking industries (Electric Arc Furnace (EAF) slag) and natural zeolite (clinoptilolite) were used as the starting materials. Preparation of an adsorbent involved two steps, namely extraction iron oxide (IO) from slag and precipitation of IO onto clinoptilolite. Characterization of NZIC were done using Fourier Transform Infrared spectroscopy (FTIR), Scanning Electron Microscopy (SEM), single-point Brunauer Emmett Teller (BET) surface area analysis, Vibrating Sample Magnetometer (VSM) and pH at zero point charge (pHzpc). The NZIC showed a lower magnetic saturation at 8.13 emu/g compared to maghemite at 29.5 emu/g. The BET surface area of NZIC was 146.29 m2/g, larger compared to the individual surface area of clinoptilolite and maghemite which are 37.84 and 17.84 m2/g respectively. Adsorption of PQ onto clinoptilolite and NZIC were investigated using a batch experiment. Surface characteristic of NZIC was investigated by pHzpc experiment showing that at pH 8.2 its electric surface charge is zero. Optimum parameters for adsorption of PQ in water were found at pH 12 with 0.01 g/10 mL of NZIC and equilibrium time of 20 minutes. Desorption experiment revealed that NZIC have a good recovery in repetitive usage for PQ removal in water.